LAW PROTECTION FOR WORKER’S UNSPECIFIED TIME WORK AGREEMENT IN PT INTER WORLD STEEL MILLS INDONESIA RELATED THEIR WORK PERIOD - Shinurad, Duto Mahardiko (Universitas Negeri Surabaya, 2020)
One of the problems in employment in Indonesia is the worker contract system that know as Unspecified Time Work Agreement between workers and the companies. The companies often make deals to extend the Unspecified Time Work Agreement without care about how long the worker has been working. The system of extending Unspecified Time Work Agreement without any certainty naturally raises unrest for workers for fear that Unspecified Time Work Agreement will no longer be extended. The Unspecified Time Work Agreement extension by the company is based on the existence of freedom of contract which frees the parties to make agreements and freedom to determine the contents of the agreement. This study aims to understand and analyze the legality of Unspecified Time Work Agreement who made by PT Interworld Steel Mills, and to understand the law protection for worker which extend the Unspecified Time Work Agreement. This research include normative juridical research which is a research by examining secondary legal source or library material. Legal material obtained from primary and secondary legal material with prescriptive analysis methods, namely the assessment of the right or wrong legal fact or legal events from the results of research. Unspecified Time Work Agreement is made based on the legal requirements agreement of article 1320 KUH Perdata. Base on article 1320 KUH Perdata, extending Unspecified Time Work Agreement could not fulfill the 4th elemen because Unspecified Time Work Agreement could no longer be extended or approved. As a form of legal protection, workers can conduct bipartite negotiations, mediation, andÂ sue to Industrial Court. Keywords : Unspecified Time Work Agreement, Worker, Law Protection.